Development Of a Fiberglass Composite Pelton Turbine for Micro-Hydropower Applications - Alfianda Gustiadinur; Nasruddin A. Abdullah; Nazaruddin Abdul Rahman; Fazri Amir (Fakultas Teknik Universitas Samudra, 2024)
The demand for electricity is continually increasing. Typically, electrical energy is generated using fossil fuels such as coal in thermal power plants. Generally, these power plants or other electricity generators supply power to densely populated areas such as large cities. Remote areas, however, often lack access to electricity due to their distance from urban centers. One solution to this issue is the development of micro-hydropower plants (MHPs). In MHPs, turbines are generally made of metal, which has high inertia and thus leads to lower efficiency. Therefore, this study replaces the turbine in an MHP with one made of fiberglass to assess the material's resistance to the water pressure in MHP operations. Based on the research conducted, the allowable stress for the fiberglass was determined to be 11.59801 MPa, with the water pressure applied to be 0.000985 MPa.